Investigation of Multi-Output Single-Switch Forward Converter in Terms of Cross-Regulation Using Weighted Control Method - Salih Dindar; Fırat Hardalac; Ertugrul Aksoy; Kubilay Ayturan (Applied Sciences)
In a single-switch forward converter, which is a type of single-input multiple-output (SIMO) DC–DC converter, voltage changes are observed at the outputs due to the current passing through the diodes, the difficulty of winding the transformer in full and half windings, differences in resistance in the windings, the presence of leakage inductance and the existence of common inductance between the windings. These voltage changes are undesirable, and cross-regulation techniques have been developed to keep the outputs at the desired value. One of these techniques, the weighted control method, in which voltage information is received from many outputs, is addressed in this article. The reason we apply this technique is to avoid additional components and their control problems. In addition, this technique is simpler and cheaper than other cross-regulation techniques. In this way, we will contribute to the literature on cross-regulation, showing that cross-regulation remains below 3.33% and circuit efficiency reaches 86.83% by using the weighted control method.